OC-021 A Retrospective Audit of Pneumococcal & Influenza Vaccination in Coeliac Disease. (4th June 2013) - Khan, J; Jennings, A; Subramanian, S
Abstract : Introduction: Patients with coeliac disease (CD) are at increased risk of mortality from sepsis. In particular, the risk of sepsis with encapsulated organisms such as Pneumococci is higher 1 . This may be a consequence of hyposplenism. Current Department of Health Green Book guidelines as well as Coeliac UK recommend vaccination against Pneumococci and influenza. We aimed to investigate whether or not patients with CD received vaccination against Pneumococci and influenza. Methods: CD patients were identified through a register of 1000 ICD-10 classified patients currently under follow up at Royal Liverpool and Broadgreen University Hospitals NHS Trust. A random sample of 250 patients was selected from the register. Electronic case notes were interrogated for demographic details as well as the most recently confirmed comorbidities. Patients of all ages were included in the study. Patients aged over 65 and patients with certain comorbidities (e.g. chronic obstructive airways disease, ischaemic heart disease, liver cirrhosis etc) were analysed separately as these patients should already be immunised against pneumococci and influenza regardless of their coeliac disease diagnosis. Immunisation status was obtained by contacting individual patient's general practitioners. The proportion of vaccinated patients were analysed according to the age groups < or > 65. Results: A total of 250 patients were included out of which we were able to obtain records for 198 patients. Of the 198 patients, 32% of patients had osteopenia and 13% of patients had one or more concurrent autoimmune illness (e.g. thyroid disease, pernicious anaemia, Sjogren's syndrome). 129 patients were < 65 years of age (M: F ratio 1: 2, median age-50, range 19–64) and 69 were > 65 (M: F ratio 1: 2, median age-73, range 65–84). In the < 65 category, we found 10 with no comorbidities necessitating vaccination which left 119 patients in the main study arm; 23 (19.3%) were vaccinated against Pneumococci and 42 (35%) against influenza. Conclusion: Very few patients with CD are vaccinated against preventable causes of sepsis such as Pneumococci. Gastroenterologists, GPs and patients need to be aware of the increased risk of sepsis and the need to administer vaccines against preventable infections in CD patients. Vaccination status should be routinely obtained during follow up visits. Due to the lack of a simple clinical test for hyposplenism and the high prevalence of hyposplenism in CD, it is worth considering pneumococcal vaccination for all CD patients at diagnosis. Disclosure of Interest: J. Khan: None Declared, A. Jennings: None Declared, S. Subramanian Speaker bureau with: Shire, Abbott and Dr Falk pharma, Conflict with: Advisory board member for Vifor Pharma and Abbott Reference: Ludvigsson JF, Olén O, Bell M, Ekbom A, Montgomery SM. Coeliac disease and risk of sepsis. Gut 2008; 57(8):1074–80.